A Mathematical Formulation of the Ricardian System - Pasinetti, Luigi L. (Review of Economic Studies, 1960)
Journal Article A Mathematical Formulation of the Ricardian System Get access Luigi L. Pasinetti Luigi L. Pasinetti Harvard University and Cambridge University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 2, February 1960, Pages 78–98, https://doi.org/10.2307/2296129 Published: 01 February 1960